Questionnaire development and determination of factors associated with knowledge, attitude and practice on provision of long-acting reversible contraception among primary healthcare workers in Kelantan - Jusoh, Nur Nabila (2024)
Background: Long-acting reversible contraception (LARC) is an important strategy in preventing unintended pregnancies, but its utilisation in Malaysia remains low. Healthcare workers (HCWs) can significantly influence LARC uptake, thus assessing their knowledge, attitude, and practice (KAP) on LARC provision is important. Objective: The aim was to assess the knowledge, attitude and practice on the provision of LARC and their associated factors among primary HCWs in Kelantan using a newly developed questionnaire. Methodology: The study was conducted from October 2022 to September 2023, involving HCWs in government health clinics in Kelantan. It is comprised of two phases. Phase 1 focused on developing and validating a new questionnaire. The questionnaire was developed through a literature review, expert consultations and discussions with HCWs. Then, the questionnaire was validated using content validity, cognitive interviews and psychometric evaluation of internal structure. The knowledge section underwent a two-parameter logistic item response theory (2-PL IRT) analysis. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted for the attitude and practice sections. This psychometric validation involved 444 randomly selected HCWs. Subsequently, Phase 2 involved a cross-sectional study assessing KAP and associated factors among 190 randomly selected HCWs from four districts in Kelantan. The newly validated self-administered questionnaire was utilised. Total scores were transformed into percentage scores. The data was then subjected to descriptive analysis and linear regression for comprehensive evaluation. The dependent variables were the KAP scores. Results: The new questionnaire, named ‘KAPP-LARC’, comprised 39 final items across three sections: 15 in knowledge, 13 in attitude and 11 in practice. The knowledge section displayed acceptable difficulty and discrimination values. The final model for the attitude and practice section exhibited satisfactory model fitness, with all factors having acceptable composite reliability, indicated by Raykov’s rho values greater than 0.60. The total mean percentage scores for knowledge, attitude and practice were 69.1%, 48.1% and 64.1%, respectively. Notably, knowledge regarding LARC provision was positively associated with being a doctor (adjusted b = 8.40; 95% CI: 3.76, 13.05; p<0.001), receiving formal LARC training (adjusted b = 7.47; 95% CI: 2.81, 12.12; p=0.002) and awareness of LARC insertion services in healthcare facilities (adjusted b = 8.92; 95% CI: 0.82, 17.02; p=0.031). Moreover, HCWs with more years of experience in Maternal and Child Health exhibited more positive attitudes (adjusted b =0.36; 95% CI: 0.23, 0.50; p<0.001) and practices (adjusted b = 0.74; 95% CI: 0.43, 1.04; p<0.001) towards LARC provision. Conclusion: The questionnaire exhibited satisfactory psychometric properties and reliability, making it a suitable instrument for assessing KAP regarding LARC provision among HCWs. Overall, the scores for knowledge and practice were relatively higher than the scores for attitude. Focusing on training, especially on nurses, awareness of service and Maternal and Child Health experience could contribute to the improvement of LARC provision.